West Nile and Usutu virus infections in wild birds admitted to rehabilitation centres in Extremadura, western Spain, 2017-2019 - Bravo, Daniel; Aguilera-Sepúlveda, Pilar; Guerrero-Carvajal, Fátima; Llorente, Francisco; Reina, David; Pérez-Martín, Juan Enrique; Jiménez-Clavero, Miguel Ángel; Frontera, Eva (Veterinary Microbiology, 2021)
10 Pág. Centro de Investigación en Sanidad Animal (CISA) West Nile virus (WNV) is an emerging flavivirus transmitted generally by mosquitoes of Culex genus. It is maintained in an enzootic life cycle where birds act as reservoir hosts. Humans and horses are also susceptible to infection, and occasionally, they suffer from neurological complications. However, they do not transmit the virus to other vectors, behaving as dead-end hosts. Sporadic WNV outbreaks observed in horses and wild birds from Extremadura (western Spain) during 2016 and 2017 seasons prompted to carry out this survey in wild birds, focused on specimens coming from two wildlife rehabilitation centres. Between October 2017 and December 2019, samples from 391 wild birds, belonging to 56 different species were collected and analysed in search of evidence of WNV infection. The analysis of serum samples for WNV-specific antibodies by ELISA, whose specificity was subsequently confirmed by virus-neutralisation test (VNT) showed positive results in 18.23 % birds belonging to 18 different species. Pelecaniformes (33.33 %), Accipitriformes (25.77 %) and Strigiformes (22.92 %) orders had the higher seroprevalences. Remarkably, WNV-specific antibodies were found in a black stork for the first time in Europe. Analysis by real time RT-PCR in symptomatic birds confirmed the presence of WNV lineage 1 RNA in griffon vulture and little owls. Specificity analysis of ELISA positive and doubtful sera was performed by differential VNT titration against WNV and two other cross-reacting avian flaviviruses found in Spain: Usutu virus (USUV) and Bagaza virus (BAGV). Only four samples showed USUV-specific antibodies (1.04 %) corresponding to three species: Eurasian eagle-owl, griffon vulture and great bustard (first detection in Europe) whereas no samples were found reactive to BAGV. Differential VNT yielded undetermined flavivirus result in 16 samples (4.17 %). This is the first study carried out on wild birds from Extremadura (western Spain). It highlights the ...